Limited risks of major congenital anomalies in children of mothers with coeliac disease: a population-based cohort study - Ban, Lu; West, Joe; Abdul Sultan, Alyshah; Dhalwani, Nafeesa N.; Ludvigsson, Jonas F.; Tata, Laila J. (Wiley, 2014)
Objective: To examine major congenital anomaly (CA) risks in children of mothers with coeliac disease (CD) compared with mothers without CD.